Multi‐omic analysis in normal colon organoids highlights MSH4 as a novel marker of defective mismatch repair in Lynch syndrome and microsatellite instability - Devall, Matthew; Ali, Mourad W.; Eaton, Stephen; Weisenberger, Daniel J.; Reilley, Matthew J.; Powell, Steven M.; Li, Li; Casey, Graham (Cancer medicine (Malden, MA), 2023)
Introduction Lynch syndrome (LS) is a hereditary condition that increases the risk of colorectal (CRC) and extracolonic cancers that exhibit microsatellite instability (MSI‐H). MSI‐H is driven by defective mismatch repair (dMMR), and approximately 15% of nonhereditary CRCs also exhibit MSI‐H. Here, we aimed to better define mechanisms underlying tumor initiation in LS and MSI‐H cancers through multi‐omic analyses of LS normal colon organoids and MSI‐H tumors. Methods Right (n = 35) and left (n = 23) colon organoids generated from normal colon biopsies at routine colonoscopy of LS and healthy individuals were subjected to Illumina EPIC array. Differentially methylated region (DMR) analysis was performed by DMRcate. RNA‐sequencing (n = 16) and bisulfite‐sequencing (n = 15) were performed on a subset of right colon organoids. CRISPR‐cas9‐mediated editing of MMR genes in colon organoids of healthy individuals was followed by quantitative PCR of MSH4. The relationship between MSH4 expression and tumor mutational burden was further explored in three independent tumor data sets. Results We identified a hypermethylated region of MSH4 in both the right and left colon organoids of LS versus healthy controls, which we validated using bisulfite‐sequencing. DMR analysis in three gastrointestinal and one endometrial data set revealed that this region was also hypermethylated in MSI‐H versus microsatellite stable (MSS) tumors. MSH4 expression was increased in colon organoids of LS versus healthy subjects and in publicly available MSI‐H versus MSS tumors across four RNA‐seq and four microarray data sets. CRISPR‐cas9 editing of MLH1 and MSH2, but not MSH6, in normal colon organoids significantly increased MSH4 expression. MSH4 expression was significantly associated with tumor mutational burden in three publicly available data sets. Conclusions Our findings implicate DNA methylation and gene expression differences of MSH4 as a marker of dMMR and as a potential novel biomarker of LS. Our study of LS colon organoids supports the hypothesis that dMMR exists in the colons of LS subjects prior to CRC.